Ant diversity studies in Acre: what we know and what we could do to know more? - Schmidt, Fernando Augusto; Costa, Marília Maria Silva da; Martello, Felipe; de Oliveira, Amanda Batista; Menezes, Andressa Silvana; Fontenele, Luane Karoline; Morato, Elder Ferreira; Oliveira, Marco Antônio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Brazil counts with one the largest ant diversity in the world. But, given its continental dimension and uneven scientific development process, there are still several gaps in the knowledge of this biodiversity. This fully applies to research on ant diversity in the state of Acre, southwestern Brazilian Amazon. Since 2014, in Acre, ants are being sampled by Rede BIA project, which aims to cover this gap. Thus, our main goal is to present the status of ant diversity studies in Acre regarding their progress and their contribution to the ant fauna knowledge, based on scientific papers and grey literature. We found 17 studies to Acre, which encompass a time range of 10 years, and a total of 338 species recorded. The studies are concentrated mainly in the southern and eastern parts of the state. Ground pitfall trap is the most used sampling technique. We point out that adding more sites to Rede BIA’s collecting efforts, plus focusing samplings in poorly studied habitats and ecosystems, especially in the western and eastern parts of the state will provide a lot of new data on ant species occurrence to Acre and to Brazil.